The STEM Method as a Pedagogical Resource of Curriculum Innovation for the Teaching of Natural Sciences in Educational Communities with Vulnerable Contexts (Docentes 2.0 Journal, 2025)
The STEM methodology has been adopted as a multidisciplinary pedagogical model that includes science, technology, engineering, and mathematics, which is useful in marginalized places with problems in the educational field. The present study aimed to examine the impact of the STEM approach as a pedagogical instrument of curricular innovation for instructing natural sciences in vulnerable communities. It was developed using the mixed convergent method, pragmatic paradigm, mixed approach, convergent triangulation design, multiple integration type, and cross-section. The population comprised students and teachers from the five Promoción Social del Norte educational institution campuses. The sample was made up of 150 students and 15 teachers. The research used surveys, interviews, and observations to measure validity. The results show an increase in the academic performance of students in science at the primary level of 7.0, an interest in the disciplines of 80%, and skills such as problem-solving and group work.On the other hand, teacher training was key, increasing to 90% to apply the STEM methodology. In conclusion, the STEM approach reduces educational inequalities, motivates students, and equips them with the necessary skills to face the challenges of the 21st century. However, its implementation requires adequate institutional support strategies, appropriate technologies, and the adoption of educational policies that improve teacher training and curricular renewal.
Keywords: STEM method; curricular innovation; natural sciences; vulnerable communities; inclusive education